Hubungan Beban Kerja Dengan Response Time Perawat Instalasi Gawat Darurat (IGD) Pada Rumah Sakit Tipe C Di Kabupaten Jember - Arif Eko Cahyono; Siswoyo Siswoyo; Muhamad Zulfatul A'la (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
The emergency room is the patients’ first stop and referral in hospital. Patient service in the emergency room requires immediate services, which are effective and efficient. The success of the nurse’s response time in handling patients can prevent damage to body organs, prevent disability and reduce mortality. This study aims to undrstand the correlation between workload and the response time of the emergency room nurse at Type C hospitals in Jember Regency. This study uses a correlational research design with a cross-sectional method. The sampling technique used total sampling technique. The result of this study indicated that the workload of the nurses in the emergency room was classified as moderate and had a response time according to the standard. The data analysis used Kendall tau-c statistical test and the p-value = 0,180. In conclusion, there was no correlation between workload and the response time of the emergency room nurse at Type C hospitals in Jember Regency. It happens because there are factors that influence the nurse’s motivation, chosen examination and treatment strategies when serving the patients. Their high motivation and hardwork make their performance better. In addition, the selection of inspection strategies and appropriate handling can make the services of the patients effective and efficient.